Experimental porcine toxoplasma gondii infection as a representative model for human toxoplasmosis - Nau, Julia; Schroten, Horst; Schwerk, Christian (Mediators of inflammation, 2017)
Porcine infections are currently not the state-of-the-art model to study human diseases. Nevertheless, the course of human and porcine toxoplasmosis is much more comparable than that of human and murine toxoplasmosis. For example, severity of infection, transplacental transmission, and interferon-gamma-induced antiparasitic effector mechanisms are similar in pigs and humans. In addition, the severe immunosuppression during acute infection described in mice does not occur in the experimentally infected ones. Thus, we hypothesise that porcine Toxoplasma gondii infection data are more representative for human toxoplasmosis. We therefore suggest that the animal model chosen must be critically evaluated for its assignability to human diseases.
Gesehen am 25.04.2018